Sympatric Speciation in Mole Rats and Wild Barley and Their Genome Repeatome Evolution: A Commentary - Eviatar Nevo; Kexin Li (Advanced Genetics, 2022)
Abstract The theories of sympatric speciation (SS) and coding and noncoding (cd and ncd =repeatome)  genome function are still contentious. Studies on SS in our two new models, “Evolution Canyon” and “Evolution Plateau”, in Israel, divergent microclimatically and geologically‐edaphically, respectively, indicated that in ecologically divergent microsites SS is a common speciation model across life from bacteria to mammals. Genomically, the intergenic ncd repeatome was and is still regarded by many biologists as “selfish,” “junk,” and non‐functional. In contrast, it is considered by the encyclopedia of DNA elements discovery as biochemically functional and regulatory, and the transposable elements were considered earlier by Barbara McClintock as “controlling elements” of genes. Remarkably, it is found that repeated elements can statistically identify significantly, the five species of subterranean mole rats of Spalax ehrenbergi superspecies adapted to increasingly arid climatic trend southward in Israel. Moreover, it is first discovered in the SS studies in two distant taxa, subterranean mole rats and wild barley, and later also in spiny mice in Israel and subterranean zokors in China, that the noncoding repeatome is genomically mirroring the image of the protein‐coding genome in divergent ecologies. It is shown that this mirroring image is statistically significant both within and between the ecologically divergent taxa supporting the hypothesis that much of the repeatome might be regulatory and selected as the protein‐coding genome by the same ecological stresses.